Donor‐derived regulatory dendritic cell infusion results in host cell cross‐dressing and T cell subset changes in prospective living donor liver transplant recipients. Issue 7 (23rd December 2020) - Macedo, Camila; Tran, Lillian M.; Zahorchak, Alan F.; Dai, Helong; Gu, Xinyan; Ravichandran, Ranjithkumar; Mohanakumar, Thalachallour; Elinoff, Beth; Zeevi, Adriana; Styn, Mindi A.; Humar, Abhinav; Lakkis, Fadi G.; et al.
Abstract: Regulatory dendritic cells (DCreg) promote transplant tolerance following their adoptive transfer in experimental animals. We investigated the feasibility, safety, fate, and impact on host T cells of donor monocyte‐derived DCreg infused into prospective, living donor liver transplant patients, 7 days before transplantation. The DCreg expressed a tolerogenic gene transcriptional profile, high cell surface programed death ligand‐1 (PD‐L1):CD86 ratios, high IL‐10/no IL‐12 productivity and poor ability to stimulate allogeneic T cell proliferation. Target DCreg doses (range 2.5–10 × 10 6 cells/kg) were achieved in all but 1 of 15 recipients, with no infusion reactions. Following DCreg infusion, transiently elevated levels of donor HLA and immunoregulatory PD‐L1, CD39, and CD73 were detected in circulating small extracellular vesicles. At the same time, flow and advanced image stream analysis revealed intact DCreg and "cross‐dressing" of host DCs in blood and lymph nodes. PD‐L1 co‐localization with donor HLA was observed at higher levels than with recipient HLA. Between DCreg infusion and transplantation, T‐bet hi Eomes hi memory CD8 + T cells decreased, whereas regulatory (CD25 hi CD127 − Foxp3 + ): T‐bet hi Eomes hi CD8 + T cell ratios increased. Thus, donor‐derived DCreg infusion may induce systemic changes in host antigen‐presenting cells and T cells potentially conducive to modulated anti‐donor immune reactivity at the time of transplant. Abstract : Pretransplant infusion of donor‐derived regulatory dendritic cells into living donor liver transplant recipients induces systemic changes in host antigen‐presenting cells and T cells potentially conducive to modulated antidonor immune reactivity at the time of transplant. See the editorial on page 2319 and the companion article on page 2387 .